Analyses of Bioretention Systems for Removal of Stormwater Pollutants - Sholagberu, Abdulkadir T.; Nuwagaba, Emmanuel; Tibenderana, Philip; Terseer, Ako; Bainomugisha, Jonan; Twesigye-omwe, Moses N.; Agwe, M. Tobby; Oluwatosin, Olofintoye O. (Journal of Ecological Engineering, 2025)
Stormwater transports directly into rivers eroded soil, animal wastes, pesticides, fertilizers and other potential pollutants. Bioretention is often designed to capture and treat it using the natural properties of soil and plants. However, selection of appropriate media structure and plants need to be adequately studied. This study investigated the performance of bioretention system in removing stormwater pollutants using Dracaena, a local plant, also called Song of India Plants. Physical model of three Columns A, B and C were developed having five layered filter media of different configurations whose materials were analyzed to meet the design standards. The plants were introduced into Columns A and C leaving out B as control experiment. The quality parameters were determined before and after treatments at ages 10, 20, 30and 40 days when Dracaena plants were introduced into bioretention models. The results showed that the bioretention model drastically improved stormwater quality by reducing values of electrical conductivity, total coliforms (TC), fecal coliforms (FC), total suspended solids (TSS) and biochemical oxygen demand (BOD) as compared to the tested raw stormwater samples. The filter media in both Columns A and C substantially reduced the pollutant levels to standard discharge limits for all parameters tested such as TSS, TC, FC, BOD and nitrates. BOD fell within the recommended standard after 20 days of treatment in Column C with considerable reduction in TC and FC by 68.9% and 75.4% respectively when compared to raw stormwater sample. However, Column C completely removed TC and FC at 40 days which are pathogen indicators in wastewater. This study would be useful to the stakeholders for sustainable stormwater treatment and management.